‘It feels like you’ve joined the university club’: the transformative potential of Fellowship recognition for professional services staff - Caroline Ball; Chris Ribchester (Journal of Learning Development in Higher Education)
This paper explores the impacts of engaging with fellowship professional recognition for third-space professionals within universities. The authors conducted ten semi-structured interviews with colleagues from four different professional areas: careers, library, technology-enhanced learning and technicians, after they had attained Fellowship recognition. Analysis revealed key themes around enhanced voice, confidence, reflection, and identity that resulted from successfully completing the fellowship process. However, translating these benefits into practice relies heavily on inclusive structures of encouragement, role models and support in making the language and expectations accessible. The findings indicate professional recognition schemes grounded in tailored guidance for support staff contexts offer significant untapped potential. Extending access requires critical examination of how well current cultures and systems value expertise across all university roles.